Stability analysis for seed yield and its component characters in fenugreek (Trigonella foenum-graecum L.) - Kole, P C (Journal of Spices and Aromatic Crops, 2005)
Fourteen genotypes of fenugreek (Trigollella foenum-graecum) were grown at Sriniketan (West Bengal) in four different environments during winter season for three consecutive years. Genotype x environment (G x E) interaction was studied for seed yield and its component characters namely, pods plant-’, seeds pod" and test weight. G x E interactions were highly significant for all the characters. Both linear and non-linear components of G x E interactions were highly significant, non-linear component being predominant for seeds pod" and seed yield plant·" while linear component was predominant for test weight. However, both linear and non-linear components were equally important for pods plant-’. The genotypes UM-129, UM-301 and UM-302 were stable.